Itsumi and Sayuri's Individuation Process in Akiyoshi Rikako's The Dark Maidens - Ningrum, Chandrawati Adji; Supsiadji, Mateus Rudi (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2024)
This study aims to analyze Itsumi and Sayuri's individuation process in Akiyoshi Rikako’s The Dark Maidens. Identify which aspects of individuation are most prominent in each character through Carl Gustav Jung's theory of the collective unconscious. The theory explains that the individuation process in the collective unconscious is made up of four archetypes, namely, ego, persona, shadow, and anima or animus. This research uses a descriptive qualitative method to deeply analyze and detail the characters' psychological development. The writer uses a psychological approach that examines how the characters experience individuation, a journey of self-discovery to preserve their societal image. The result of this study shows that both Itsumi and Sayuri present a persona to society, masking their true selves and hiding their shadow, the darker aspects of their personalities, within the subconscious. Itsumi's betrayal leads her ego to be overtaken by her shadow, revealing a vengeful and rebellious nature that dismantles her facade. The shadow also consumes Sayuri's ego due to her treacherous tendencies and desire to eliminate Itsumi, causing her persona to collapse. The finding of this study is the shadow's dominance results in both characters exhibiting irrational and destructive behaviors. Additionally, the characters become aware of their animus. Finally, the study concludes that the novel illustrates how individuals can undergo a negative individuation process characterized by the shadow's dominance over the ego.